Trend, Cycle, and Non-linear Trade-off in the Euro Area 1970-2001 (FEP Working Paper Nº 122, Faculdade de Economia da Universidade do Porto, Março 2003) - Álvaro Aguiar (2003)
This paper presents new tests and estimates of the Phillips trade-off in the Euro Area, carried out in a unobserved components model with possibly non-linear Phillips and Okun relations, using quarterly aggregate data for the period 1970:I-2001:II. A concept of forward-looking near-rational expectations is introduced in the model, improving on the contradiction between rational expectations and evidence of inflation inertia. The Phillips curve turns out to be linear and its trade-off statistically significant, while non-linearity shows up in the Okun relation. The trend-cycle decompositions capture the main features of the Euro Area recente macroeconomic record.